Investigation of apomorphine during sleep in Parkinson’s: Improvement in UPDRS Scores - Miguel A. Pieroni (Neurology International, 2019)
Sleep is responsible for several functions required for homeostasis. REM sleep could be a rearrangement period where limits of certain functions can be moved to a new state of balance. This study proposes that dopaminergic deficit may be responsible for the circadian dysregulation that occur with neurodegeneration and therefore a restitution of REM sleep and an improvement in Parkinson disease’s symptoms can be achieved with the controlled use of dopamine agonists during the night. Twenty parkinsonian patients underwent to a onemonth study of subcutaneous nocturnal apomorphine treatment at the beginning of each REM stage. This therapeutic approach led to a significant benefit for patients in all of the 3 UPDRS scores. The mean change from baseline in the MDS-UPDRS Part I, II and III was significantly greater in the apomorphine vs. placebo group. In the UPDRS Part I total score was 0.8 (95% confidence interval [CI]: 1.612, -0.012) and 3.3 (95% CI: 4.732, 1.867) for the placebo and apomorphine groups, respectively (difference between groups: 2.5, 95% CI: 3.454, 1.545; P = 0.002). For UPDRS Part II total score, the mean change was 1.3 (95% CI: 2.692, - 0.09) and 4.6 (6.916, 2.28). Difference between groups: 3.3, 95% CI: 4.752, 1.847; P = 0.013. In UPDRS Part III was 1.1 (95% CI: 2.425, -0.225) and 5.5 (95% CI: 8.808, 2.191). Difference between groups: 4.4, (95% CI: 6.321, 2.478; P = 0.012). We can conclude that sleep alteration in PD can be improved by stimulation of D2 receptors. The symptomatic benefits obtained due to restoration of REM functions were significant.